Extinct species - Grolier Educational (Danbury, Conn Grolier Educational, 2002)
Examines extinct species, including prehistoric man, and discusses why extinction happens, as well as how information is gathered on species that existed before humans evolved
1. Why extinction occurs -- 2. Prehistoric animal life -- 3. Fossil hunting -- 4. Extinct mammals -- 5. Extinct birds -- 6. Extinct underwater life -- 7. Extinct reptiles and amphibians -- 8. Extinct invertebrates and plants -- 9. Hominids -- 10. Atlas of extinction
Hurg
5 8
Keywords: Extinct animals -- Juvenile literature; Extinct animals; Extinction (Biology); Extinction (Biology) -- Juvenile literature